The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1002/cncr.30819
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent body mass index and risk of colon and rectal cancer in a cohort of 1.79 million Israeli men and women: A population‐based study

Abstract: Being overweight or obese in adolescence was associated with an increased risk of subsequent colon cancers in men and women, whereas obesity was associated with rectal cancer. Cancer 2017;123:4022-30. © 2017 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
1
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 44 publications
(132 reference statements)
1
45
1
2
Order By: Relevance
“…Thus, we likely underestimated the actual proportions of cancers attributable to some individual risk factors and all potentially modifiable factors combined. Furthermore, some risk factors may be more important when exposure occurs in adolescence or earlier, such as excess body weight and colorectal cancer, which are likely unaccounted for by RRs from studies of mostly older adults. More research is needed on earlier life exposures that can increase the risk of cancer in adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we likely underestimated the actual proportions of cancers attributable to some individual risk factors and all potentially modifiable factors combined. Furthermore, some risk factors may be more important when exposure occurs in adolescence or earlier, such as excess body weight and colorectal cancer, which are likely unaccounted for by RRs from studies of mostly older adults. More research is needed on earlier life exposures that can increase the risk of cancer in adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…Although BMI tracks the body weight of an individual well over time in general, a single measurement of BMI in midlife or later is not sufficient to represent the impact of adiposity in early life or of weight change during key periods in life . As described previously, emerging evidence suggests that excess body weight in early life is associated with increased risk of several cancers, including colorectal, endometrial, pancreatic, and thyroid cancers as well as multiple myeloma . Nevertheless, most studies assumed a 10‐year lag period between excess body weight and cancer occurrence, which is a likely underestimate of the latency period required for the multistage carcinogenesis process.…”
Section: Global Burden Of Cancers Attributable To Excess Body Weightmentioning
confidence: 99%
“…Additionally, larger body size in childhood and adolescence is associated with increased risk of non-Hodgkin's lymphoma later in life (6). A recent study that investigated cancer rates in a cohort of 1.79 million Israeli men and women over a median of 23 years reported that increased BMI in adolescence was associated with increased risk of colorectal and rectal cancer (7). The mechanisms by which obesity increases cancer risk remain to be fully elucidated.…”
Section: Introductionmentioning
confidence: 99%